Editorial Notes and Archaeological Events - al-Asil, Naji
Expedition of Prof. Braidwood – The German Archaeological Expedition for Warka – The British Expedition at Nimrud — The Japanese Institute of Oriental Studies – The Assyrian Palace at Nebi Yunus.